The Laplace transform of Dirichlet L-functions - Balčiūnas, Aidas; Laurinčikas, Antanas (Nonlinear Analysis: Modelling and Control, 2012)
In the paper, a formula for the Laplace transform of the square of Dirichlet L-functions on the critical line is obtained.